(untitled) (Research, Society and Development, 2025)
Lung cancer remains one of the leading causes of cancer-related mortality worldwide, largely due to late diagnosis, tumor heterogeneity, and therapeutic resistance. Liquid biopsy, particularly through the analysis of circulating tumor DNA (ctDNA), has emerged as a promising tool for disease detection and monitoring. This study synthesizes scientific evidence published between 2022 and 2025 regarding the use of circulating cell-free DNA (cfDNA) and circulating tumor DNA (ctDNA) as non-invasive biomarkers in lung cancer. A total of 30 studies were selected from national and international databases. Findings show that ctDNA has strong potential for early detection, minimal residual disease (MRD) assessment, recurrence prediction, therapeutic monitoring, and prognostic evaluation, especially when combined with technologies such as methylation profiling, fragmentomics, and nucleosome mapping. Despite these advances, methodological variability, high costs, and unequal access still limit widespread clinical implementation, particularly in middle-income countries. In conclusion, ctDNA represents a promising tool for advancing precision oncology, but requires further investment, multicenter validation, and public policies that support equitable adoption.